Controlled Drug Release: Photocatalytic Degradation of Cell Membrane Coatings for Controlled Drug Release (Adv. Healthcare Mater. 12/2016). Issue 12 (22nd June 2016) - Rao, Lang; Meng, Qian‐Fang; Huang, Qinqin; Liu, Pei; Bu, Lin‐Lin; Kondamareddy, Kiran Kumar; Guo, Shi‐Shang; Liu, Wei; Zhao, Xing‐Zhong
Abstract : Controlled drug release is significant for preventing drug resistance. As described by W. Liu and co‐workers on page 1420, core‐shell SiO2 @TiO2 nanoparticles with enhanced photocatalytic activity can be applied in for UV‐light‐triggered degradation of surface erythrocyte membrane coatings, demonstrating the potential of using biomimetic cell‐membrane‐coated nanocarriers for controlled drug delivery.